COMPARISON OF PLAQUE INDEX IN PATIENTS WITH CANCER WHO ARE UNDERGOING CHEMOTHERAPY BASED ON THE FREQUENCY - Widodo, Widodo; Adhani, Rosihan; Zakia, Rahma (FKG Unlam, 2017)
Background: One of the main cancer treatments is chemotherapy â a systemic treatment of cancer.Chemotherapy can kill cancer cells quickly, however it can also kill the healthy cells in human body. The morechemotherapy is done, the more cancer cells are damaged, and so are the healthy cells. One of the healthy cellsthat will be affected is oral cavity cells which can cause side effects, like xerostomia. Chemotherapy drugs aretoxic and it can lead to destructive effects on salivary glands. Xerostomia can cause the reduced function ofsaliva as self-cleansing, thus it can be one factor to facilitate the forming of plaque. Purpose: The objective ofthis research is to identify the difference of plaque index score on cancer patients who are undergoingchemotherapy based on the frequency in RSUD Ulin Banjarmasin. Method: This research uses expost factomethod with cross sectional approach. The samples of this research are 80 patients with cancer who areundergoing chemotherapy. Result: The data is tested by using nonparametric Kruskal Wallis test with p<0.05(p=0.001) shows that there is a meaningful difference of plaque index score within each group. Conclusion:According to the research that has been conducted, it can be concluded that there is a meaningful difference ofplaque index score in patients with cancer who are undergoing chemotherapy based on their frequency.